4

5 (x + 2) = 4 ( x + 3)

5x + 10 = 4x + 12

5x - 4x = 12 -10

x = 2

Added 7/21/2012 11:19:13 AM

3

7( x - 6 ) + 4 ( x + 3) = 3

7x - 42 + 4x + 12 = 3

11x - 30 = 3

11x = 33

x = 33/11

x = 3

Added 7/21/2012 11:20:10 AM

0

[Deleted]

Added 7/22/2012 2:53:21 AM

0

5(x+2)=4(x+3)

5x+10=4x+12

5x-4x=12-10

x=2

Added 7/22/2012 2:54:31 AM

This answer has been flagged as incorrect.

0

5(x + 2) = 4 ( x + 3) implies 5x +10 = 4x + 12 implies 5x - 4x = 12- 10 implies x= 2.

Therefore answer is x=2

Added 7/22/2012 3:48:24 AM

This answer has been flagged as incorrect.

0

5(x+2) = 4(x+3)

5x + 10 = 4x + 12

get variables to one side by subtracting 4x from both sides

5x - 4x + 10 = 4x - 4x +12

x + 10 = 12

Now get the 10 to the the right side by subtractin 10 from each side

x + 10 - 10 = 12 -10

solve to get your answer

x = 2

Added 7/22/2012 4:04:46 PM

This answer has been flagged as incorrect.